Infectious mononucleosis (Epstein-Barr virus infection) and chronic hepatitis - Lejla Čalkić; Lejla Bajramović-Omeragić; Adnan Mujezinović (Medicinski glasnik, 2019)
Aim: To describe a case of an eight-year-old boy with chronic Epstein-Barr virus (EBV) hepatitis with incipient cirrhosis, rarely found in practice. Methods: The diagnosis was based on findings of specific IgG serum antibodies and EBV positive liver biopsy. Other etiologies of hepatitis were excluded: autoimmune hepatitis, viral hepatitis A, B, or C, cytomegalovirus (CMV), herpes simplex virus (HSV), adenovirus infection, toxoplasma infection. Results: A mild form of infectious mononucleosis with acute hepatitis without icterus was found in the boy first time at the age of three. He got sick again in april 2018 with fever, minor loss of appetite and weakness, skin and sclera were anicteric, no enlarged neck lymph nodes. Ultrasonography of the spleen revealed a spleen diameter of 10.7 cm, while the liver was 11.8 cm. Laboratory findings, sedimentation, blood count, C reactive protein (CRP) were all normal. Ten days and a month later an increase of aminotransferase was noticed. The liver biopsy and PCR EBV DNA were performed six months of disease onset. The disease had lasted for about one more year with loss of strength and an increase of aminotransferase with maximum value of 3-4 times higher than normal one. The therapy was supportive. Conclusion: Chronic EBV hepatitis is very rare. In differential diagnosis of hepatitis and unclear febrile conditions, EBV infection should not be forgotten.
Keywords: biopsy; differential diagnosis; liver cirrhosis